Design and Analysis of the Suspension Upright Structure of a Formula SAE Car - Muhammad Izzat Nor, Ma'arof; Vong, Ratanakvisal; Lim, Jin Wei; Amir Radzi, Ab Ghani; Girma, Tadesse Chala (INTI International University, 2019)
The suspension system is one of the most important parts of a vehicle. It plays an important role in the absorptions of shocks and impacts. It also determines the safety and rigidity of the rear and front arm connection of vehicle. The objective of this study was to design a new suspension system for a Formula SAE Competition. The scope and parameters are identified with the selection of a racing car wheel and tires and availability of current resources from previous research projects such as car chassis and lower and upper double A-arm. The upright structure was designed in certain steps to reduce weight by minimizing the surface area at the same time by considering the strength of the material. Results showed that the geometry with the lowest stress is at 8.037 MPa with a length of 220 mm and width of 120 mm. The simulation provided a concrete data of how the structure behave with different dimensions but also the most critical point is attaining the equivalent stress of the designed structure. For future studies, improvements can be done by changing the parameters and conduct experimental method to see any deviations from the theoretical/simulation results.